2013
DOI: 10.1051/0004-6361/201220494
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical investigation of severalQpasteroids and their relation to the Vesta family

Abstract: Context. To take advantage of the large dataset provided by the SDSS data, recently a new taxonomic scheme was proposed designed to be compatible with previous taxonomies. One interesting feature in this distribution is the large number of Q p asteroids scattered all around the main belt with a marked concentration in the Vesta region, where the V p are found most frequently. Since the mineralogy and thermal evolution traditionally related to the classical Q-and V-type taxonomic classes (and by construction th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…Those asteroids that lie above the olivine-orthopyroxene trend line in Figure 4, with the exception of (36118) 1999 RE 135 , have relatively large amounts of olivine or clinopyroxene present on their surfaces, which excludes them from classification as likely basaltic asteroids. Jasmin et al (2013) reported an NIR spectrum for (7302) 1993 CQ that is very similar to our spectrum in Figure 2. Their reported band parameters (Band I: 0.958 μm; Band II: 1.914 μm; BAR: 0.566) are broadly consistent with our results, although our reported band centers and BAR values are marginally larger.…”
Section: Outer-belt V P Asteroidssupporting
confidence: 76%
See 2 more Smart Citations
“…Those asteroids that lie above the olivine-orthopyroxene trend line in Figure 4, with the exception of (36118) 1999 RE 135 , have relatively large amounts of olivine or clinopyroxene present on their surfaces, which excludes them from classification as likely basaltic asteroids. Jasmin et al (2013) reported an NIR spectrum for (7302) 1993 CQ that is very similar to our spectrum in Figure 2. Their reported band parameters (Band I: 0.958 μm; Band II: 1.914 μm; BAR: 0.566) are broadly consistent with our results, although our reported band centers and BAR values are marginally larger.…”
Section: Outer-belt V P Asteroidssupporting
confidence: 76%
“…(26417) Michaelgord displays a much shallower increase in reflectance across the same spectral range but is also spectrally featureless. However, Jasmin et al (2013) report an NIR spectrum and analysis for (11699) 1998 FL 105 that are consistent with a basaltic surface composition. Verification of the basaltic nature of (11699) 1998 FL 105 will require additional observations, but our results should be taken as provisional, pending verification of the presence of rotational variations in the asteroid's NIR spectra.…”
Section: Groupmentioning
confidence: 82%
See 1 more Smart Citation
“…1 is clear that there is an excess of observations classified as Q p at low phase angles and a deficit of observations with this classification at higher phase angles, with the reverse occurring for the S p and V p classes. This effect was originally noted by Jasmim et al (2013) when analyzing Q p asteroids in the Vesta family. Considering the classes without band, the observations classified as C p are also more frequent at low phase angles and missing at higher phase angles, while the opposite is true for the observations with D p class, and the distribution of observations with X p class more closely reproduces the distribution of all observations.…”
Section: Effects On Taxonomic Classificationmentioning
confidence: 69%
“…While analyzing the distribution of SDSS-based taxonomies (Carvano et al 2010;Hasselmann et al 2011) in the Vesta family, Jasmim et al (2013) recently noted a considerable number of asteroids classified as Q p , along with the dominant V p class. Mineralogy inferred from near-infrared (NIR) spectra of a sample of V p and Q p in the family showed that although the Q p asteroids presented a shallower 1 µm band than the V p asteroids, their silicate mineralogy was essentially the same.…”
Section: Introductionmentioning
confidence: 99%